Stochastic morphological swings in Hydra regeneration: A manifestation of noisy canalized morphogenesis - Oded Agam; Erez Braun (Proceedings of the National Academy of Sciences, 2025)
Animal morphogenesis, the development of an organism’s body form, is commonly perceived as a directed and almost deterministic process. However, noise and stochastic fluctuations are ubiquitous in biological systems. The questions on the role of fluctuations in morphogenesis and what ensures the robustness of this process under noisy conditions remain elusive. Here, we utilize Hydra regeneration, subjected to an external electric field, to provide unique insights into these questions. We found that during Hydra morphogenesis, a phase can be induced where fluctuations lead to stochastic morphological swings, back and forth, between a nearly spherical structure (the incipient tissue’s state) and an elongated cylindrical shape (the final body form of a mature Hydra ). Despite these prolonged swings, the tissue regenerates into a normal Hydra . The stochastic transitions between two well-defined shapes imply that morphological development occurs through an activation process. Indeed, by introducing a periodic perturbation through modulation of the electric field, we were able to demonstrate morphogenesis dynamics with characteristics of stochastic resonance —the tissue’s response to the perturbation displayed a resonance-like behavior as a function of the noise level. Our findings add a dynamic layer to the problem of morphogenesis and offer an unconventional physical framework based on an activation transition in a slowly varying double-well potential that ensures a canalized regeneration of the body form under fluctuations.